The Importance of Universities of Applied Sciences for Regional Development – Theory and empirical Evidence for the German Middle Lower Rhine Area - Ruediger Hamm; Martin Wenke (European Regional Science Association (ERSA), 2001)
The existence of an adequate research- and development-environment is seen as a locational factor of extraordinary importance for a region. A university of applied sciences as one component of such an environment should be able to influence the innovation behaviour of enterprises positively, although those universities traditionally are noticed as educational institutions. But the education of students can be interpreted as a "supply side effect of those universities, too, because education of students and further education of employees will improve the regions equipment with human capital and so will yield a higher labour productivity. Additionally the transfer of knowledge from science to the entrepreneurial practice is able to increase productivity within the region in question. Another aspect is the strengthening of the adjustment flexibility of regions regarding processes of structural change. The flexibility will be the higher, the higher the qualification level of employees is. The last aspect of universities of applied science in opposite to (ordinary) universities is their stronger regional orientation. The educational supply especially is directed to younger people, who are living in the region. As a result the existing reserves of talents will be exhausted as best as possible. The paper is organised as follows: First a classification of regional supply side effects as mentioned above as well as demand side effects (income and employment effects of the institutions activities) will be presented. In the second part of the paper estimation results of income and employment effects of the University of Applied Sciences Lower Rhine on the basis of a regional multiplier analysis will be described. Supply side effects of this university have been evaluated by using the results of an enterprise poll. In the third part results of that poll about the enterprises knowledge, notices and assessments of the university activities are presented as well as the innovation behaviour of the enterprises and the related impacts of the university. The paper closes with a summary and suggestions regarding further research.
Keywords: 330